Cutaneous Horn of the Glans - Camilla Santos Ribeiro; David Rubem Azulay; Danielle Carvalho Quintella; Tullia Cuzzi; Marcia Ramos- (Karger Publishers, 2021)
Cutaneous horn is a protuberance constituted by compact keratinous material, with a hard consistence similar to a horn, which occurs more frequently in photoexposed areas. The authors describe a case of cutaneous horn on the glans considered a rare location. Verrucous carcinoma was the histopathological diagnosis of the base of the horn and lichen sclerosis, the precursor lesion.